Mortality of the Pregnant Women with COVID-19 at Referral Hospitals in Central Java, Indonesia - Sutopo Patria Jati; Cipta Pramana; Bambang Wibowo; Hery Sudjagat; Murni Murni (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Pregnant women have a high potential for infectious infections including Covid-19. This study focused on analysing the characteristics and outcomes of 95 maternal deaths that were caused by COVID-19. This observational-retrospective study descriptively analysed 95 maternal deaths due to COVID-19. The study was conducted in June – July 2021 at the COVID-19 Referral hospitals in Central Java Province. The study found that the majority of these deaths occurred in women between the ages of 20 to 35, with 74% falling in this age range. Furthermore, the study found that 63.2% of the patients required treatment for more than 48 hours. The study also noted that almost all of the women who died (98.9%) had not been vaccinated against COVID-19. Of the patients who received treatment, 73.7% received standard therapy. Additionally, 55.8% of the patients had a moderate condition when admitted to the hospital. More than half of the patients (52.6%) died in the intensive care unit (ICU). Furthermore, 63.2% of the patients arrived at the hospital alone. This data may suggest that some of these women were not receiving adequate support or medical care before their hospitalisation.